A kind of phosphorus-doped titanium dioxide and its preparation method and application
By depositing and calcining titanium dioxide and silica on black phosphorus nanosheets, phosphorus-doped titanium dioxide nanomaterials were prepared, which solved the problem of low photocatalytic efficiency of titanium dioxide photocatalysts and achieved efficient light absorption and catalytic performance improvement.
Patent Information
- Application Number
- CN202310329421.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-30
AI Technical Summary
The existing titanium dioxide photocatalysts limit their photocatalytic efficiency due to the wide optical band gap and the rapid recombination of photoexcited carriers. Metal doping leads to thermodynamic instability, and non-metal doping may lead to crystal phase transformation and particle size increase, reducing Catalytic activity.
Titanium dioxide and silica were deposited on black phosphorus nanosheets by sol-gel method, and phosphorus-doped titanium dioxide nanomaterials with large specific surface area, uniform particle size and adjustable crystallinity were prepared through calcination and etching, and black phosphorus doping was collected and doped into Titanium dioxide lattice, silica protects titanium dioxide from agglomeration and excessive growth.
The photocatalytic performance of titanium dioxide is improved, the light absorption range is broadened to visible light and infrared light, the photogenerated electron-hole recombination rate is reduced, and the effect of maximizing the use of sunlight is achieved.
Smart Images

Figure CN116273088B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysis, and specifically relates to phosphorus-doped titanium dioxide and a preparation method and application thereof. Background Art
[0002] Since the first discovery of titanium dioxide photocatalytic water decomposition in 1972, photocatalytic technology has attracted widespread attention due to its use of inexhaustible green solar energy to solve the crisis of energy shortage and environmental pollution. 1-3 Titanium dioxide has the advantages of good chemical stability, strong redox ability, low cost and non-toxicity. It has been widely used in the fields of photocatalytic hydrogen and oxygen release, carbon dioxide reduction, decomposition of harmful substances, nitrogen fixation and organic synthesis. 4-9 However, the inherent wide optical band gap of TiO2 and the rapid recombination of photoexcited carriers greatly limit its photocatalytic efficiency.
[0003] In order to solve the above two shortcomings, recent research has focused on partially replacing Ti by doping metals (Ce, Ni, Ag, Pt, Fe, etc.) and non-metals (C, N, S, Si). 4+ and O 2- , thereby improving its performance 10-23 The role of metal doping is to promote the separation of photogenerated carriers and reduce their recombination rate. The role of non-metal doping is to move the absorption region of titanium dioxide from the ultraviolet region to the visible light region, while narrowing the band gap of titanium dioxide. In 2020, Chiara Alberoni et al. 2 To adjust the electronic properties of nano-titanium dioxide, nanotube (CeTNTx) and nanoparticle (CeTNPx) photocatalysts were prepared. 10 The results show that the addition of Ce leads to a decrease in the energy gap, thereby increasing the visible light absorption rate. 2 When the doping amount is 0.25wt%, the degradation rate of methylene blue (MB) of nanotubes and nanoparticles is the highest (0.123min -1 and 0.146min -1 ), and complete degradation was achieved in 120 minutes. In 2012, S. Krejcíkováa et al. used nonionic surfactant Triton X-114, cyclohexane, AgNO 3 Silver-doped TiO was prepared by sol-gel method using aqueous solution and metal precursor as raw materials. 2 Photocatalyst 16 Compared with pure titanium dioxide catalyst, the absorption spectrum of silver-doped titanium dioxide catalyst shifts to the visible light region, and the absorption of CO 2In 2021, Maria Sadia et al. used titanium isopropoxide as a precursor to synthesize nickel-doped and non-doped titanium dioxide photocatalysts. 18 . Studies have shown that nickel-doped titanium dioxide catalysts have higher catalytic degradation efficiency in neutral red and methylene blue due to reduced photogenerated electron-hole recombination rate. In 2018, Wenyi Huang et al. prepared a high-concentration N-doped anatase titanium dioxide photocatalyst using a low-temperature non-aqueous solvothermal method. 14 . Studies have shown that during the synthesis process, N atoms penetrate into the titanium dioxide lattice, forming impurity energy levels in the forbidden band of titanium dioxide, enhancing the absorption of visible light and having excellent performance in the photocatalytic degradation of methylene blue. In 2012, Jian-Wen Shi et al. used carbon spheres as templates and adopted a simple method to synthesize C-doped titanium dioxide hollow spheres (THS) 19 . Studies have shown that C doping narrows the band gap of titanium dioxide and produces sub-bandgap absorption, which leads to the photoresponse of THS to visible light and shows higher photocatalytic activity for the decomposition of methylene blue than commercial P25. In 2017, Zhenyu Huang et al. synthesized S-TiO using thiourea dioxide as the sulfur source and reducing agent. 2-x Photocatalyst 15 The study showed that S doping leads to the 2-x The absorption edge of Ti is red-shifted. 3+ The introduction of S-TiO forms a localized state at the bottom of the conduction band. 2-x It can absorb visible light. In addition, Ti 3+ As an electron capture agent, it improves the conductivity of the photocatalyst and accelerates the transfer of electrons and holes. 2 Compared with photocatalysts, S-TiO 2-x The photocatalyst showed excellent photocatalytic activity for the degradation of rhodamine B under visible light irradiation. In 2018, Zhenbiao Dong et al. reduced Ti-Si-O nanotubes on titanium-silicon alloys with zinc under Ar atmosphere to obtain black silicon-doped nanotubes, which were used as photoanodes for photoelectrochemical (PEC) water splitting. 12 The results show that due to the introduction of Si and Ti into the nanotubes 3+ / O vacancies, which improves light absorption and promotes the separation of photogenerated electron-hole pairs. The light conversion efficiency can reach 1.22%, which is the highest among undoped TiO 2 The light conversion efficiency is 7.18 times higher.
[0004] The existing technical solutions reduce the bandgap width of titanium dioxide by metal / non-metal doping, reduce the recombination rate of photogenerated electrons and holes, enhance the absorption of visible light by titanium dioxide, and improve the photocatalytic performance of titanium dioxide. However, at the same time, metal ion doping will cause thermodynamic instability of titanium dioxide and introduce some photogenerated carrier recombination centers, which will reduce the performance of the catalyst to a certain extent. Doping with non-metallic elements such as C and N will bring about problems such as the transformation of the titanium dioxide crystal phase, the increase of nanoparticle size, and the reduction of specific surface area, which will cause the activity of the catalyst to decrease.
[0005] References
[0006] 1. Duan, Y.; Wang, Y.; Gan, L.; Meng, J.; Feng, Y.; Wang, K.; Zhou, K.; Wang, C.; Han, X.; Zhou, X., Amorphous Carbon Nitride with Three Coordinate Nitrogen (N 3 C)Vacancies for Exceptional NOx Abatement in Visible Light. Advanced EnergyMaterials 2021,11(19).
[0007] 2. Fujishima, A.; Honda, K., Electrochemical Photolysis of Water at a Semiconductor Electrode. Nature 1972, 238(5358), 37-38.
[0008] 3.Li,H.;Zhang,X.;MacFarlane,DR,Carbon Quantum Dots / Cu2OHeterostructures for Solar-Light-Driven Conversion of CO 2 toMethanol.Advanced Energy Materials 2015,5(5).
[0009] 4.Bhethanabotla,V.C.;Russell,D.R.;Kuhn,J.N.,Assessment of mechanismsfor enhanced performance of Yb / Er / titania photocatalysts for organicdegradation:Role of rare earth elements in the titania phase.AppliedCatalysis B:Environmental 2017,202,156-164.
[0010] 5.Gao,M.;Connor,P.K.N.;Ho,G.W.,Plasmonic photothermic directedbroadband sunlight harnessing for seawater catalysis and desalination.Energy&Environmental Science 2016,9(10),3151-3160.
[0011] 6.Kuo,T.-R.;Liao,H.-J.;Chen,Y.-T.;Wei,C.-Y.;Chang,C.-C.;Chen,Y.-C.;Chang,Y.-H.;Lin,J.-C.;Lee,Y.-C.;Wen,C.-Y.;Li,S.-S.;Lin,K.-H.;Wang,D.-Y.,Extended visible to near-infrared harvesting of earth-abundant FeS 2 –TiO 2 heterostructures for highly active photocatalytic hydrogen evolution.GreenChemistry 2018,20(7),1640-1647.
[0012] 7.Tian,J.;Hao,P.;Wei,N.;Cui,H.;Liu,H.,3D Bi2MoO6 Nanosheet / TiO 2Nanobelt Heterostructure:Enhanced Photocatalytic Activities andPhotoelectochemistry Performance.ACS Catalysis 2015,5(8),4530-4536.
[0013] 8.Wang,M.;Han,Q.;Zhou,Y.;Li,P.;Tu,W.;Tang,L.;Zou,Z.,TiO2nanosheet-anchoring Au nanoplates:high-energy facet and wide spectra surface plasmon-promoting photocatalytic efficiency and selectivity for CO 2 reduction.RSCAdvances 2016,6(85),81510-81516.
[0014] 9.Yu,J.;Yang,Y.;Fan,R.;Wang,P.;Dong,Y.,Enhanced photovoltaicperformance of dye-sensitized solar cells using a new photoelectrodematerial:upconversion YbF 3 -Ho / TiO2nanoheterostructures.Nanoscale 2016,8(7),4173-4180.
[0015] 10.Alberoni,C.; I.;Infantes-Molina,A.; E.;Talon,A.;Zhao,H.;You,S.;Vomiero,A.;Moretti,E.,Ceria doping boostsmethylene blue photodegradation in titania nanostructures.Materials ChemistryFrontiers 2021,5(11),4138-4152.
[0016] 11.Belver,C.;Bedia,J.; M.A.;Rodriguez,J.J.,Solarphotocatalytic purification of water with Ce-doped TiO 2 / clayheterostructures.Catalysis Today 2016,266,36-45.
[0017] 12.Dong,Z.;Ding,D.;Li,T.;Ning,C.,Black Si-doped TiO 2 nanotubephotoanode for high-efficiency photoelectrochemical water splitting.RSC Adv2018,8(11),5652-5660.
[0018] 13.Eadi,S.B.;Kim,S.;Jeong,S.W.;Jeon,H.W.,Novel Preparation of FeDoped TiO 2 Nanoparticles and Their Application for Gas Sensor andPhotocatalytic Degradation.Advances in Materials Science and Engineering2017,2017,1-6.
[0019] 14.Huang,W.;Cheng,H.;Feng,J.;Shi,Z.;Bai,D.;Li,L.,Synthesis ofhighlywater-dispersible N-doped anatase titania based on low temperature solvent-thermal method.Arabian Journal of Chemistry 2018,11(6),871-879.
[0020] 15.Huang,Z.;Gao,Z.;Gao,S.;Wang,Q.;Wang,Z.;Huang,B.;Dai,Y.,Facilesynthesis ofS-doped reduced TiO 2-xwith enhanced visible-light photocatalyticperformance.Chinese Journal of Catalysis 2017,38(5),821-830.
[0021] 16. S.;Matějová,L.; K.;Obalová,L.;Matěj,Z.; L.; O.,Preparation and characterization of Ag-doped crystalline titania forphotocatalysis applications.Applied Catalysis B:Environmental 2012,111-112,119-125.
[0022] 17.Ren,R.;Wen,Z.;Cui,S.;Hou,Y.;Guo,X.;Chen,J.,Controllable Synthesisand Tunable Photocatalytic Properties of Ti(3+)-doped TiO2.Sci Rep 2015,5,10714.
[0023] 18.Sadia,M.;Naz,R.;Khan,J.;Zahoor,M.;Ullah,R.;Khan,R.;Naz,S.;Almoallim,H.S.;Alharbi,S.A.,Metal doped titania nanoparticles as efficientphotocatalyst for dyes degradation.Journal of King Saud University-Science2021,33(2).
[0024] 19.Shi,J.-W.;Chen,J.-W.;Cui,H.-J.;Fu,M.-L.;Luo,H.-Y.;Xu,B.;Ye,Z.-L.,One template approach to synthesize C-doped titania hollow spheres with highvisible-light photocatalytic activity.Chemical Engineering Journal 2012,195-196,226-232.
[0025] 20.Vijayan,B.K.;Dimitrijevic,N.M.;Wu,J.;Gray,K.A.,The Effects of PtDoping on the Structure and Visible Light Photoactivity of TitaniaNanotubes.The Journal of Physical Chemistry C 2010,114(49),21262-21269.
[0026] 21.Wu,Q.;Huang,F.;Zhao,M.;Xu,J.;Zhou,J.;Wang,Y.,Ultra-small yellowdefective TiO 2 nanoparticles for co-catalyst free photocatalytic hydrogenproduction.Nano Energy2016,24,63-71.
[0027] 22.Xiong,Y.;He,D.;Jaber,R.;Cameron,P.J.;Edler,K.J.,Sulfur-Doped CubicMesostructured Titania Films for Use as a Solar Photocatalyst.The Journal ofPhysical Chemistry C2017,121(18),9929-9937.
[0028] 23.Yao,L.;Wang,H.;Zhang,Y.;Wang,S.;Liu,X.,Fabrication of N dopedTiO 2 / C nanocomposites with hierarchical porous structure and high photocatalytic activity.Microporous and Mesoporous Materials 2019,288. Summary of the invention
[0029] In order to solve the problems in the prior art, the present invention provides a method for preparing phosphorus-doped titanium dioxide. The phosphorus-doped titanium dioxide prepared by the method provided by the present invention further improves the photocatalytic performance of titanium dioxide by preparing a titanium dioxide nanomaterial having the characteristics of large specific surface area, high uniformity of particle size, adjustable crystallinity and controllable crystal phase.
[0030] The method for preparing phosphorus-doped titanium dioxide comprises the following steps:
[0031] S1: Titanium dioxide is deposited on black phosphorus nanosheets using a sol-gel method to obtain a black phosphorus / titanium dioxide composite material.
[0032] S2: Depositing silicon dioxide on the black phosphorus / titanium dioxide composite material prepared in S1 to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material.
[0033] S3: calcining and etching the black phosphorus / titanium dioxide / silicon dioxide composite material obtained in S2.
[0034] Furthermore, step S1 includes:
[0035] S11: according to the amount of C mg of black phosphorus, a corresponding amount of black phosphorus nanosheet solution is weighed, washed three times with anhydrous ethanol, dispersed in D mL of ethanol, added with E mL of anhydrous acetonitrile, and under stirring, added with F mL of concentrated ammonia to obtain solution a;
[0036] S12: G mL of anhydrous ethanol, H mL of anhydrous acetonitrile and 1 mL of tetrabutyl titanate (TBOT) were mixed to obtain solution b;
[0037] S13: Stir solution a at room temperature for 5-10 minutes, then quickly add solution b into it, stir for more than 4 hours, centrifuge, wash four times with anhydrous ethanol, and disperse in 30 ml of ethanol to obtain a black phosphorus / titanium dioxide composite material (i.e., BP@TiO 2 sample),
[0038] Among them, C:D:E:F:G:H:I=(15~30):(20~30):(5~10):(0.1~0.5):(2~5):(0.5~2):(0.05~0.5).
[0039] Furthermore, step S2 includes:
[0040] The black phosphorus / titanium dioxide composite material (BP@TiO 2 The sample was added with polyacrylic acid (PAA, 0.01 g / mL), stirred for more than 2 hours, centrifuged, washed with anhydrous ethanol, and dispersed in J mL ethanol. K mL water, L mL concentrated ammonia, and M mL tetraethyl orthosilicate (TEOS) were added thereto, stirred for more than 4 hours, centrifuged, washed with ethanol and water, and dried to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material (BP@TiO 2 @SiO 2 Sample), where J:K:L:M=(20~30):(2~5):(0.5~2):(0.5~2).
[0041] Specifically, the mass fraction of the ammonia solution is 25-28%, and the drying temperature is 60-70°C.
[0042] Furthermore, step S2 includes:
[0043] The black phosphorus / titanium dioxide / silicon dioxide composite material obtained in step S2 was calcined for 2 h under an argon atmosphere and cooled to room temperature to obtain the calcined BP@TiO 2 @SiO 2 sample;
[0044] Take N mg calcined BP@TiO 2 @SiO 2 The sample was dissolved in 0 mL P 2.5 mol / L sodium hydroxide solution, stirred at 50 °C for nearly 8 hours, centrifuged, washed with water to obtain phosphorus-doped titanium dioxide, dried and set aside.
[0045] Among them, N:O:P=(50~500):(20~50):(0.5~3).
[0046] Specifically, the calcination temperature is 600-800°C, and the drying temperature is 60-70°C.
[0047] Furthermore, the method for preparing phosphorus-doped titanium dioxide comprises a step S0 before the step S1:
[0048] Prepare black phosphorus nanosheets by electrochemical exfoliation method: Ag tetrabutylammonium bromide (TBAB) is dissolved in B mL N,N-dimethylformamide (DMF) as electrolyte, black phosphorus crystal is cathode, platinum electrode is counter electrode, tetrabutylammonium bromide is intercalation agent, after electrolysis for about 5 hours, centrifuge to collect the product, wash it four times with DMF and disperse it in DMF. Store in glove box for future use, wherein A:B=(2~4):(50~100).
[0049] One object of the present invention is to provide phosphorus-doped titanium dioxide. The phosphorus-doped titanium dioxide is prepared according to any of the above methods for preparing doped titanium dioxide.
[0050] An object of the present invention is to provide a use of the phosphorus-doped titanium dioxide as described above in photocatalysis.
[0051] The present invention coats a titanium dioxide layer and silicon dioxide on a black phosphorus nanosheet by a sol-gel method and then performs protective calcination. During the calcination process, the two advantages of black phosphorus being doped into the titanium dioxide lattice and silicon dioxide effectively protecting the agglomeration and excessive growth of titanium dioxide grains are combined, and phosphorus-doped titanium dioxide nanomaterials with characteristics such as large specific surface area, high uniformity of particle size, adjustable crystallinity and controllable crystal phase can be prepared. Phosphorus-doped titanium dioxide nanomaterials have the characteristics of narrow bandgap width and low recombination rate of photogenerated electrons and holes. The light absorption range is broadened to visible light and infrared light, which further improves the photocatalytic performance of titanium dioxide and achieves the effect of maximizing the use of sunlight. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 A scanning electron microscope (SEM) image of the black-scale nanosheet provided in Example 3 of the present invention;
[0053] Figure 2 A scanning electron microscope (SEM) image of the black phosphorus / titanium dioxide composite material provided in Example 3 of the present invention;
[0054] Figure 3 The X-ray diffraction (XRD) pattern of phosphorus-doped titanium dioxide provided in Example 3 of the present invention;
[0055] Figure 4 This is a STEM-EDS scanning image of phosphorus-doped titanium dioxide provided in Example 3 of the present invention;
[0056] Figure 5 The UV-visible spectrogram of rhodamine provided in Examples 2 and 3 of the present invention. DETAILED DESCRIPTION
[0057] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings, but they should not be construed as limiting the applicable scope of the present invention.
[0058] The present invention adopts a brand-new method to prepare phosphorus-doped titanium dioxide nanomaterials. Based on the characteristics of black phosphorus nanosheets such as large specific surface area, it is proposed to use black phosphorus (BP) nanosheets with a large specific surface area as a growth template for titanium dioxide, and deposit amorphous titanium dioxide and silicon dioxide layers thereon in sequence by a sol-gel method. By utilizing the effective protection calcination of silicon dioxide, effective phosphorus doping of titanium dioxide is achieved, and the particle size, crystal phase, crystallinity and other properties of titanium dioxide are controlled to prepare a phosphorus-doped titanium dioxide photocatalyst with excellent performance. Through the combined effect of phosphorus doping and silicon dioxide protection calcination, the titanium dioxide nanomaterial obtained has the characteristics of large specific surface area, uniform particle size, controllable crystal phase, etc., has a small bandgap width, and a low photogenerated electron-hole recombination rate, so as to fully utilize visible light and near-infrared light, and maximize the use of solar energy.
[0059] The method for preparing phosphorus-doped titanium dioxide comprises the following steps:
[0060] S1: Titanium dioxide is deposited on black phosphorus nanosheets using a sol-gel method to obtain a black phosphorus / titanium dioxide composite material.
[0061] S2: Depositing silicon dioxide on the black phosphorus / titanium dioxide composite material prepared in S1 to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material.
[0062] S3: calcining and etching the black phosphorus / titanium dioxide / silicon dioxide composite material obtained in S2.
[0063] In one embodiment, black phosphorus nanosheets are prepared by the following steps:
[0064] S0: Preparation of black phosphorus nanosheets by electrochemical exfoliation: Ag tetrabutylammonium bromide (TBAB) was dissolved in B mL N,N-dimethylformamide (DMF) as the electrolyte, black phosphorus crystals were used as the cathode, platinum electrode was used as the counter electrode, and tetrabutylammonium bromide was used as the intercalation agent. After electrolysis for about 5 hours, the product was collected by centrifugation, washed four times with DMF, and then dispersed in DMF. It was stored in a glove box for future use. Among them, A:B = (2-4): (50-100). The concentration of black phosphorus was determined by spectroscopy.
[0065] In one embodiment, step S1 includes:
[0066] S11: Prepare solution a: weigh a corresponding amount of black phosphorus nanosheet solution according to the amount of C mg black phosphorus, wash it three times with anhydrous ethanol, disperse it in D mL ethanol, add E mL anhydrous acetonitrile, and add F mL ammonia water under stirring to obtain solution a.
[0067] S12: Prepare solution b: mix G mL of anhydrous ethanol, H mL of anhydrous acetonitrile and 1 mL of tetrabutyl titanate (TBOT) to obtain solution b.
[0068] S13: Stir solution a at room temperature for 5-10 minutes, then quickly add solution b into it, stir for more than 4 hours, centrifuge, wash four times with anhydrous ethanol, and disperse in 30 ml of ethanol to obtain a black phosphorus / titanium dioxide composite material (i.e., BP@TiO 2 sample).
[0069] Among them, C:D:E:F:G:H:I=(15~30):(20~30):(5~10):(0.1~0.5):(2~5):(0.5~2):(0.05~0.5).
[0070] In one embodiment, step S2 includes:
[0071] The black phosphorus / titanium dioxide composite material (BP@TiO 2 The sample was added with polyacrylic acid (PAA, 0.01 g / mL), stirred for more than 2 hours, centrifuged, washed with anhydrous ethanol, and dispersed in J mL ethanol. K mL water, L mL ammonia water, and M mL tetraethyl orthosilicate (TEOS) were added thereto, stirred for more than 4 hours, centrifuged, washed with ethanol and water, and dried to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material (BP@TiO 2 @SiO 2 Sample). Among them, J:K:L:M=(20~30):(2~5):(0.5~2):(0.5~2).
[0072] In one embodiment, step S3 includes:
[0073] The black phosphorus / titanium dioxide / silicon dioxide composite material obtained in step S2 was heated to the required temperature under argon atmosphere and calcined for 2 h, and then cooled to room temperature to obtain the calcined BP@TiO 2 @SiO 2 Sample. Take N mg calcined BP@TiO 2 @SiO 2 The sample was dissolved in 0 mL P 2.5 mol / L sodium hydroxide solution, stirred at 50 °C for nearly 8 hours, centrifuged, and washed with water to obtain the etched phosphorus-doped titanium dioxide (BP@TiO 2 Sample), dried and set aside, wherein N:O:P=(50-500):(20-50):(0.5-3).
[0074] In one embodiment, phosphorus-doped titanium dioxide and a method for preparing the same include the following steps:
[0075] S0: Preparation of black phosphorus nanosheets by electrochemical exfoliation: Ag tetrabutylammonium bromide (TBAB) was dissolved in B mL N,N-dimethylformamide (DMF) as the electrolyte, black phosphorus crystals were used as the cathode, platinum electrode was used as the counter electrode, and tetrabutylammonium bromide was used as the intercalation agent. After electrolysis for about 5 hours, the product was collected by centrifugation, washed four times with DMF, and then dispersed in DMF. It was stored in a glove box for future use. Among them, A:B = (2-4): (50-100). The concentration of black phosphorus was determined by spectroscopy.
[0076] S1: Depositing titanium dioxide on black phosphorus nanosheets by a sol-gel method to obtain a black phosphorus / titanium dioxide composite material. Specifically, the method comprises the following steps:
[0077] S11: Prepare solution a: weigh a corresponding amount of black phosphorus nanosheet solution according to the amount of C mg black phosphorus, wash it three times with anhydrous ethanol, disperse it in D mL ethanol, add E mL anhydrous acetonitrile, and add F mL concentrated ammonia under stirring to obtain solution a.
[0078] S12: Prepare solution b: G mL of anhydrous ethanol, H mL of anhydrous acetonitrile, and 1 mL of tetrabutyl titanate (TBOT) to obtain solution b.
[0079] S13: Stir solution a at room temperature for 5-10 minutes, then quickly add solution b into it, stir for more than 4 hours, centrifuge, wash four times with anhydrous ethanol, and disperse in 30 ml of ethanol to obtain a black phosphorus / titanium dioxide composite material (i.e., BP@TiO 2 sample).
[0080] Among them, C:D:E:F:G:H:I=(15~30):(20~30):(5~10):(0.1~0.5):(2~5):(0.5~2):(0.05~0.5).
[0081] S2: Depositing silicon dioxide on the black phosphorus / titanium dioxide composite material prepared in S1 to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material. Specifically, the process comprises the following steps:
[0082] The black phosphorus / titanium dioxide composite material (BP@TiO 2 The sample was added with polyacrylic acid (PAA, 0.01 g / mL), stirred for more than 2 hours, centrifuged, washed with anhydrous ethanol, and dispersed in J mL ethanol. K mL water, L mL concentrated ammonia, and M mL tetraethyl orthosilicate (TEOS) were added thereto, stirred for more than 4 hours, centrifuged, washed with ethanol and water, and dried to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material (BP@TiO 2 @SiO 2Sample). Among them, J:K:L:M=(20~30):(2~5):(0.5~2):(0.5~2).
[0083] Optionally, the mass fraction of the ammonia solution is 25-28%, and the drying temperature is 60-70°C
[0084] S3: calcining and etching the black phosphorus / titanium dioxide / silicon dioxide composite material obtained in S2. Specifically, the process comprises the following steps:
[0085] The black phosphorus / titanium dioxide / silicon dioxide composite material obtained in step S2 was heated to the required temperature under argon atmosphere and calcined for 2 h, and then cooled to room temperature to obtain the calcined BP@TiO 2 @SiO 2 Sample. Take N mg calcined BP@TiO 2 @SiO 2 The sample was dissolved in 0 mL P 2.5 mol / L sodium hydroxide solution, stirred at 50 °C for nearly 8 hours, centrifuged, and washed with water to obtain the etched phosphorus-doped titanium dioxide (BP@TiO 2 Sample), dried and set aside, wherein N:O:P=(50-500):(20-50):(0.5-3).
[0086] Optionally, the calcination temperature is 600-800°C and the drying temperature is 60-70°C.
[0087] The present invention provides Examples 1-3, all of which are prepared according to the above-mentioned phosphorus-doped titanium dioxide preparation method, the difference is that the amounts of reagents used are different, specifically refer to the following table:
[0088]
[0089]
[0090] The black scale nanosheets prepared in Examples 1-3 were subjected to electron microscope scanning tests; the black phosphorus / titanium dioxide composite material prepared in Example 3 was subjected to electron microscope scanning tests; the phosphorus-doped titanium dioxide prepared in Examples 1-3 was subjected to X-ray diffraction tests; the phosphorus-doped titanium dioxide prepared in Example 3 was subjected to STEM-EDS scanning tests.
[0091] The scanning electron microscope (SEM) image of the black scale nanosheet prepared in Example 3 is as follows: Figure 1 As shown, the scanning electron microscope (SEM) images of the black scale nanosheets prepared in Example 1-2 are similar to Figure 1 Similar, by Figure 1 It can be seen that the black phosphorus nanosheets were successfully peeled off from the bulk black phosphorus crystals, have good dispersion, and most of them are single-layer nanosheets.
[0092] The scanning electron microscope (SEM) image of the black phosphorus / titanium dioxide composite material prepared in Example 3 is as follows: Figure 2 As shown, through Figure 1 It can be seen from the comparison that titanium dioxide is successfully coated on the surface of black phosphorus nanosheets to form a black phosphorus / titanium dioxide composite material.
[0093] The X-ray diffraction (XRD) pattern of phosphorus-doped titanium dioxide prepared in Example 3 is as follows: Figure 3 As shown, the X-ray diffraction (XRD) pattern of phosphorus-doped titanium dioxide prepared in Example 1-2 is similar to Figure 3 Similar, from Figure 3 It can be seen that the prepared phosphorus-doped titanium dioxide is anatase phase, and as the amount of precursor TBOT increases, the prepared phosphorus-doped titanium dioxide has a better crystal structure.
[0094] The STEM-EDS scanning image of phosphorus-doped titanium dioxide prepared in Example 3 is as follows: Figure 4 As shown, Ti, O, Na, Si, and P elements were observed in the figure, indicating the successful doping of P element into titanium dioxide.
[0095] The present invention also provides a use of the phosphorus-doped titanium dioxide in photocatalysis.
[0096] The catalytic performance of the phosphorus-doped titanium dioxide prepared in Examples 1-3 was evaluated by the rate of degradation of rhodamine B.
[0097] Evaluation method: The photocatalytic activity was evaluated by tracking the degradation of Rhodamine B (RhB) over time. The phosphorus-doped titanium dioxide catalyst was dispersed in a Rhodamine B (RhB) aqueous solution (20 mL, 1×10-5 M) and stirred for 30 min under dark conditions to ensure the adsorption of Rhodamine B dye on the surface of the phosphorus-doped titanium dioxide catalyst. The excitation source was a 300W xenon lamp, and the concentration of RhB was determined using a UV-visible spectrophotometer. The concentration of Rhodamine B in the reaction medium was tracked as a function of time using the intensity of the 553nm absorption peak to obtain Figure 5 The catalytic performance data reported in Figure 5 (Left) shows the catalytic efficiency of phosphorus-doped titanium dioxide prepared in Example 2. After 90 minutes of illumination, the degradation efficiency of rhodamine reached 94%; Figure 5 (Right) shows the degradation efficiency of phosphorus-doped titanium dioxide prepared in Example 3. After 30 minutes of illumination, rhodamine is degraded by about 90%. The phosphorus-doped titanium dioxide prepared in Example 1 also has a high degradation efficiency for rhodamine.
[0098] The present invention coats a titanium dioxide layer and silicon dioxide on a black phosphorus nanosheet by a sol-gel method and then performs protective calcination. During the calcination process, the two advantages of black phosphorus being doped into the titanium dioxide lattice and silicon dioxide effectively protecting the agglomeration and excessive growth of titanium dioxide grains are combined, and titanium dioxide nanomaterials with characteristics such as large specific surface area, uniform particle size, adjustable crystallinity and controllable crystal phase can be prepared. Phosphorus-doped titanium dioxide nanomaterials have the characteristics of reducing the narrow bandgap and low photogenerated electron-hole recombination rate, and the light absorption range is broadened to visible light and infrared light, which further improves the photocatalytic performance of titanium dioxide and achieves the effect of maximizing the use of sunlight.
Claims
1. A method for preparing phosphorus-doped titanium dioxide, characterized in that: The following steps are involved: S1: Depositing titanium dioxide on black phosphorus nanosheets by a sol-gel method to obtain a black phosphorus / titanium dioxide composite material, S1 comprises: S11: according to the amount of C mg of black phosphorus, a corresponding amount of black phosphorus nanosheet solution is weighed, washed three times with anhydrous ethanol, dispersed in D mL of ethanol, added with E mL of anhydrous acetonitrile, and under stirring, added with F mL of concentrated ammonia to obtain solution a; S12: G mL of anhydrous ethanol, H mL of anhydrous acetonitrile and 1 mL of tetrabutyl titanate are mixed to obtain solution b; S13: Stir solution a at room temperature for 5-10 minutes, then quickly add solution b thereto, stir for more than 4 hours, centrifuge, wash four times with anhydrous ethanol, and disperse in 30 mL of ethanol to obtain the black phosphorus / titanium dioxide composite material. Among them, C: D: E: F: G: H: I = (15~30): (20~30): (5~10): (0.1~0.5): (2~5): (0.5~2): (0.05~0.5); S2: depositing silicon dioxide on the black phosphorus / titanium dioxide composite material prepared in S1 to obtain a black phosphorus / titanium dioxide / silicon dioxide composite material, S2 comprises: Add polyacrylic acid to the black phosphorus / titanium dioxide composite material obtained in step S1, stir for more than 2 hours, centrifuge and wash with anhydrous ethanol, disperse in J mL ethanol, add K mL water, L mL ammonia water and M mL tetraethyl orthosilicate thereto, stir for more than 4 hours, centrifuge, wash with ethanol and water, and dry to obtain the black phosphorus / titanium dioxide / silicon dioxide composite material, wherein J: K: L: M = (20-30): (2-5): (0.5-2): (0.5-2); S3: calcining and etching the black phosphorus / titanium dioxide / silicon dioxide composite material obtained in S2, S3 includes: The black phosphorus / titanium dioxide / silicon dioxide composite material obtained in step S2 is heated to calcine for 2 h in an argon atmosphere, and then cooled to room temperature to obtain a calcined black phosphorus / titanium dioxide / silicon dioxide sample; Take N mg of the calcined black phosphorus / titanium dioxide / silicon dioxide sample and dissolve it in O mL P mol / L sodium hydroxide solution, stir it at 50° C. for 8 hours, centrifuge it, and wash it with water to obtain the phosphorus-doped titanium dioxide. Among them, N:O:P = (50~500): (20~50): (0.5~3).
2. The method for preparing phosphorus-doped titanium dioxide according to claim 1, characterized in that: The mass fraction of the ammonia water in step S2 is 25-28%, and the drying temperature is 60-70°C.
3. The method for preparing phosphorus-doped titanium dioxide according to claim 1, characterized in that: The calcination temperature is 600-800°C, and the drying temperature is 60-70°C.
4. The method for preparing phosphorus-doped titanium dioxide according to claim 1, characterized in that: Including the S0 step before the S1 step: Black phosphorus nanosheets were prepared by electrochemical stripping method: Ag tetrabutylammonium bromide was dissolved in B mL N,N-dimethylformamide DMF as electrolyte, black phosphorus crystal was used as cathode, platinum sheet electrode was used as counter electrode, tetrabutylammonium bromide was used as intercalation agent. After electrolysis for 5 hours, the product was collected by centrifugation, washed four times with DMF, dispersed in DMF, stored in glove box for later use, wherein A: B = (2~4): (50~100).
5. A phosphorus-doped titanium dioxide, characterized in that: The method for preparing phosphorus-doped titanium dioxide is described in any one of claims 1 to 4.
6. Use of the phosphorus-doped titanium dioxide as claimed in claim 5 in photocatalysis.
Citation Information
Patent Citations
Phosphor doping type nano titanium dioxide having efficient sunlight catalytic capability and preparation method thereof
CN101690896A
Preparation method of novel photocatalyst S-doped SiO2 / TiO2 composite material
CN102302940A
Hollow nanometer particle titanium dioxide / black phosphinidene photothermal catalyst as well as preparation method and application thereof
CN108514887A
Method for preparing polycrystalline black phosphorus nanosheets by hydrothermal etching method
CN110950313A
Spherical bismuth vanadate / black phosphorus composite photocatalyst and preparation method thereof
CN112076769A
Cited By
Preparation method of phosphorus-doped defect type titanium dioxide hydrogel and application of phosphorus-doped defect type titanium dioxide hydrogel to treatment of indoor formaldehyde
CN118022848A
